2012
DOI: 10.1186/1476-511x-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic and linoleic acids induce ER stress and apoptosis in hepatoma cells

Abstract: ObjectivesHepatic inflammation and degeneration induced by lipid depositions may be the major cause of nonalcoholic fatty liver disease. In this study, we tried to investigate the effects of saturated and unsaturated fatty acids on hepatoma cell apoptosis.MethodsH4IIE liver cells were treated with palmitic acid, linoleic acid, or both with or without the calcium-specific chelator BAPTA-AM after which the expression of proteins associated with endoplasmic reticulum (ER) stress, apoptosis, caspase-3 levels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 23 publications
14
115
1
1
Order By: Relevance
“…Maize kernel contains an average fatty acid composition of 11 % palmitic (16:0), 2 % stearic (18:0), 24 % oleic (18:1), 62 % linoleic (18:2) and 1 % linolenic (18:3) acids (Weber, 1987). Unsaturated fatty acids are considered healthier because they have a positive influence on reducing serum cholesterol and low density lipoproteins (Mattson and Grundy, 1985), as well as on preventing degenerative diseases and cancer (Mattson and Grundy, 1985;Zhang et al, 2012). On the other hand, increased saturated (palmitic and stearic) fatty acids can enable production of margarines without hydrogenation and the subsequent formation of undesirable trans fatty acids (Duvick et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Maize kernel contains an average fatty acid composition of 11 % palmitic (16:0), 2 % stearic (18:0), 24 % oleic (18:1), 62 % linoleic (18:2) and 1 % linolenic (18:3) acids (Weber, 1987). Unsaturated fatty acids are considered healthier because they have a positive influence on reducing serum cholesterol and low density lipoproteins (Mattson and Grundy, 1985), as well as on preventing degenerative diseases and cancer (Mattson and Grundy, 1985;Zhang et al, 2012). On the other hand, increased saturated (palmitic and stearic) fatty acids can enable production of margarines without hydrogenation and the subsequent formation of undesirable trans fatty acids (Duvick et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that PA induces ER stress in many different cell species [39][40][41]. We wondered whether PA treatment causes ER stress to cultured HAECs by determining the expression of CHOP, a marker of ER stress response [42].…”
Section: Pa Increases Et-1 Expression Through the Induction Of Er Strmentioning
confidence: 99%
“…Some fatty acids attenuate growth and induce apoptosis in a variety of human cancer cell lines [3][4][5]8,9,13,14,[16][17][18]. Fatty acid-induced apoptosis may be correlated with increased activity of caspases [4,7,16,17].…”
Section: Discussionmentioning
confidence: 96%
“…Some fatty acids such as polyunsaturated linoleic acid and saturated palmitic acid are known to induce ER stress [13]. To investigate whether x-HUA treatment causes ER stress, ER-specific signals were measured.…”
Section: X-hua-caused Activation Of Er Stress Signalsmentioning
confidence: 99%